TNF transactivation of EGFR stimulates cytoprotective COX-2 expression in gastrointestinal epithelial cells - Hobbs, Stuart S. (American Physiological Society, 2011)
TNF and epidermal growth factor (EGF) are well-known stimuli of cyclooxygenase (COX)-2 expression, and TNF stimulates transactivation of EGF receptor (EGFR) signaling to promote survival in colon epithelial cells. We hypothesized that COX-2 induction and cell survival signaling downstream of TNF are mediated by EGFR transactivation. TNF treatment was more cytotoxic to COX-2(−/−) mouse colon epithelial (MCE) cells than wild-type (WT) young adult mouse colon (YAMC) epithelial cells or COX-1(−/−) cells. TNF also induced COX-2 protein and mRNA expression in YAMC cells, but blockade of EGFR kinase activity or expression inhibited COX-2 upregulation. TNF-induced COX-2 expression was reduced and absent in EGFR(−/−) and TNF receptor-1 (TNFR1) knockout MCE cells, respectively, but was restored upon expression of the WT receptors. Inhibition of mediators of EGFR transactivation, Src family kinases and p38 MAPK, blocked TNF-induced COX-2 protein and mRNA expression. Finally, TNF injection increased COX-2 expression in colon epithelium of WT, but not kinase-defective EGFR(wa2) and EGFR(wa5), mice. These data indicate that TNFR1-dependent transactivation of EGFR through a p38- and/or an Src-dependent mechanism stimulates COX-2 expression to promote cell survival. This highlights an EGFR-dependent cell signaling pathway and response that may be significant in colitis-associated carcinoma.